Poems of Coleridge - Coleridge, Samuel Taylor, 1772-1834; Symons, Arthur, 1865-1945 (Salt Lake City, UT : Project Gutenberg, 2005)
"Poems of Coleridge" by Samuel Taylor Coleridge is a collection of poetry that showcases the lyrical prowess of one of the key figures of the early 19th century Romantic movement. The book features both famous poems like "The Rime of the Ancient Mariner" and "Christabel," as well as a selection of others that explore themes of love, nature, and the human condition. Coleridge$1 (Bs works reflect his deep emotional sensitivity and philosophical musings, establishing him as a pivotal voice in English literature. The opening of "Poems of Coleridge" presents an introduction by Arthur Symons, who provides insight into Coleridge's unique approach to love and friendship, illustrating the internal struggles that influenced his writing. He elaborates on Coleridge's relationships, particularly with fellow poet William Wordsworth, highlighting how these connections shaped his creative output. The reader is introduced to the profound complexity of Coleridge's emotions and thoughts, leading into the monumental poem "The Rime of the Ancient Mariner," which tells the haunting tale of a mariner$1 (Bs supernatural journey and penance after he recklessly kills an albatross. The opening sets the stage for an exploration of the intricate interplay between emotion, imagination, and reality within Coleridge's poetry. (This is an automatically generated summary.)s
Release date is 2005-06-01
Jonathan Ingram, Jerry Fairbanks and the Online Distributed Proofreading Team
Keywords: English poetry